TANTANGAN DAN HARAPAN BAHASA GALIK PADA ERA-MILENIAL - NFN Martina (Balai Bahasa Kalimantan Barat, 2019)
Millenial era has a major influence on people's lives. Science and technology is growing so rapidly, so that everyone tries to fit themselves with the existed changes and advances including the adoption of language. Regarding language adoption, the problem that arises now is that speakers of regional languages turn to use other languages when returning to their home areas. Therefore, this study highlights the challenges and expectations of Galik in the millennial era. The method used is the descriptive method with a qualitative approach. The data is collected by doing observation and interview. The collected data is then classified and analyzed according to the problem raised. The results of the study show that the challenges faced by speakers of Galik in these eras, namely the change of attitude of the educated speakers toward the language when returning to their hometowns. The language attitude of the community and Galik scholars in influenced by the environment and outside knowledge. The language used by the educated speakers has undergone a shift when communicating with people in their environment. They tend to use languages that considered more modern and prestigious in their environment, namely Indonesian, Malay, Javanese, Ribun, and English.